Early cognitive basic symptoms are accompanied by neurocognitive impairment in patients with an 'at‐risk mental state' for psychosis. Issue 4 (12th May 2016) - Eisenacher, Sarah; Rausch, Franziska; Ainser, Fabian; Englisch, Susanne; Becker, Anna; Mier, Daniela; Fenske, Sabrina; Meyer‐Lindenberg, Andreas; Kirsch, Peter; Zink, Mathias
Abstract: Aim: Patients with an increased risk for psychosis ('at‐risk mental state' (ARMS)) present various neurocognitive deficits. Not least because of differences in identifying the ARMS, results of previous studies are inconsistent. In most studies ARMS‐patients are classified by the experience of attenuated psychotic symptoms (APS) and/or brief limited intermittent psychotic symptoms (BLIPS). Few studies additionally assessed cognitive basic symptoms (BS). A comprehensive assessment in the very early stage of the ARMS is missing. Methods: In the present study we characterized ARMS‐patients for cognitive BS (ARMS‐BS), APS and BLIPS (ARMS‐A/B) according to the Early Recognition Inventory based on IRAOS (ERIraos). Furthermore, we assessed neurocognitive deficits using the MATRICS consensus cognitive battery for schizophrenia with a primary hypothesis regarding working memory performance. Groups of 38 ARMS‐patients and 38 healthy controls were matched for age, gender, education and premorbid verbal intelligence. Results: Between‐group comparisons revealed significant poorer working memory performance in addition to lower verbal learning and problem solving, slower processing speed and lower global neurocognitive functioning in ARMS‐patients as compared to controls. ARMS‐BS did not differ from ARMS‐A/B. Conclusions: These results underscore the presence of cognitive limitations in patients only presenting with cognitive BS. Knowledge of these early cognitive deviations supports the inclusion of early ARMS‐stages into a comprehensive concept of the psychosis risk state. Therapeutic interventions already applied at this stage might prevent deterioration of constraints. Longitudinal and interventional studies investigating the interaction of cognitive BS and neurocognitive as well as metacognitive deficits are warranted.